2023
DOI: 10.1002/jbmr.4821
|View full text |Cite
|
Sign up to set email alerts
|

Global Epidemiology of Hip Fractures: Secular Trends in Incidence Rate, Post‐Fracture Treatment, and All‐Cause Mortality

Abstract: In this international study, we examined the incidence of hip fractures, postfracture treatment, and all‐cause mortality following hip fractures, based on demographics, geography, and calendar year. We used patient‐level healthcare data from 19 countries and regions to identify patients aged 50 years and older hospitalized with a hip fracture from 2005 to 2018. The age‐ and sex‐standardized incidence rates of hip fractures, post‐hip fracture treatment (defined as the proportion of patients receiving anti‐osteo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(33 citation statements)
references
References 30 publications
(46 reference statements)
1
15
0
Order By: Relevance
“…18-20 Overall, however, the suspected number of hip fractures globally is expected to double, consistent with our study findings. 21 Examination of potential reasons behind falling incidence rates in some countries again strongly points to the importance of population-level interventions, such as increased physical activity, reduced smoking rates, and greater uptake of osteoporotic medication prescriptions. 22…”
Section: Discussionmentioning
confidence: 99%
“…18-20 Overall, however, the suspected number of hip fractures globally is expected to double, consistent with our study findings. 21 Examination of potential reasons behind falling incidence rates in some countries again strongly points to the importance of population-level interventions, such as increased physical activity, reduced smoking rates, and greater uptake of osteoporotic medication prescriptions. 22…”
Section: Discussionmentioning
confidence: 99%
“…Beyond mortality, hospital-acquired infection is associated with increased length of hospital stay and cost to healthcare systems [9]. The incidence of hip fractures continues to rise, with incidence predicted to almost double from 2018 to 2050 [10]. It is therefore important to improve our understanding of factors that can increase the risk of post-operative complications, including infection, and the measures that can be put in place to prevent these.…”
Section: Introductionmentioning
confidence: 99%
“…Temporal association with an increased risk of CVEs has been observed in different disease populations, such as gout 4 , influenza-like illness 5 and hip fracture 6 . The incidence of hip fracture, a significant public health concern, was projected to double by 2050 compared to 2018 7 . A meta-analysis of observational studies 8 further confirmed the association between hip fracture and an increased risk of CVEs.…”
Section: Introductionmentioning
confidence: 99%